Defending Against Cyber Threats: Analyzing Challenges and Security Frameworks - Vandita Dipak Shah; Asst. Prof. Nimesh Vaidya; Dr. Vijaykumar B Gadhavi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Cybersecurity plays a crucial role in the digital news industry. One of the key challenges in today’s competitive landscape is ensuring the security of news content. The increasing prevalence of cybercrimes is a major concern whenever digital protection is considered. Without robust security measures, critical assets such as plans, confidential files, and other essential data remain vulnerable. Every organization, whether an IT company or a non-technical business, requires equal protection. Attackers continuously evolve their tactics, leveraging advanced and sophisticated techniques to exploit vulnerabilities across various industries. Given the vast amounts of data stored and utilized by sectors such as defense, government, commerce, healthcare, and social services, digital security is of utmost importance. Sensitive information, including business records, classified intelligence, proprietary innovations, and personal data, must be safeguarded to prevent unauthorized access, which could lead to severe consequences.